The Nomogram of Clitoral Length and Width in Iranian Term and Preterm Neonates - Alaei, Mohammadreza; Rohani, Farzaneh; Norouzi, Elahe; Hematian Boroujeni, Nahid; Tafreshi, Roya Isa; Salehiniya, Hamid; Soheilipour, Fahimeh (Frontiers in Endocrinology, 2020)
Background and objectives: Clitoromegaly is an important parameter in the evaluation of ambiguous genitalia in neonates, but the normative data for clitoral size in newborns has racial / ethnic differences. The present study aimed to determine clitoral length (CL) and clitoral width (CW) values and stablish cut-off measurement to define clitoromegaly in both term and preterm Iranian neonates for the first time. Methods: A total number of 580 female newborn infants delivered at 28 to 42 weeks of gestation were enrolled in the study and their CL and CW measured on the first 72 hours of birth. Data about birth weight (BW), body length (BL) and head circumferences (HC) of newborns, mothers’ age, and gestational age (GA) were recorded, too. Results were presented as mean ± SD for quantitative variables and were summarized by frequency (percentage) for categorical variables. Backward stepwise regression analysis was used for prediction of CL and CW. Results: Among 580 Iranian female newborns studied, 187 were term neonates and other 393 newborns were preterm. Mean ± SD of clitoris length were 6.11 ± 0.39 mm in term infants and 5.45 ± 0.64 mm in preterm infants (P <0.001). Mean ± SD of clitoris width was 4.22 ± 0.43 in term infants and was 3.68 ± 0.53 in preterm infants (P < 0.001). Regression analysis showed that clitoris length was correlated with gestational age considered by last menstrual period, BL, BW, and HC; and clitoris width was associated with GA, BL and BW. Conclusion: This study suggests normative values (mean + 1, 2, and 3SD) of clitoral length and width according to gestational age, which can be used as a reference for Middle East’s newborns, especially Iranian newborn babies.